Determinants of CO2 Emissions: Evidence from United States - Indanazulfa Qurrota A’yun; Devi Anggrayni (Universitas Darussalam Gontor, 2023)
The decline in environmental quality can be marked by an increase in the earth's temperature or what we call global warming. Global warming can be caused by increasing concentrations of greenhouse gas (GHG) emissions on earth, one of the most important components of which is CO2 emissions. This study aims to determine the effect of economic growth, energy consumption, forest areaand urbanization on CO2 emissions in Indonesia in the period 1970-2020. This study uses a Vector Error Correction Model (VECM) analysis model. The results of the study indicate that economic growth, energy consumption, and foreign direct investment have a significant effect on CO2 emissionsin the long term.